Diagnostic utility of central node necrosis in predicting extracapsular spread among oral cavity squamous cell carcinoma. Issue 1 (29th January 2014) - Randall, Derrick R.; Lysack, John T.; Hudon, Marc E.; Guggisberg, Kelly; Nakoneshny, Steven C.; Wayne Matthews, T.; Dort, Joseph C.; Chandarana, Shamir P.
ABSTRACT Background Oral cavity squamous cell carcinoma (SCC) represents the most common SCC affecting the head and neck region. Long‐term survival of patients with oral cavity SCC is adversely affected by lymph node metastasis and further decreased by the presence of lymph node extracapsular spread (ECS). Methods Using a case‐control design, preoperative CT scans from patients with oral cavity SCC and metastatic lymphadenopathy were evaluated by 2 independent neuroradiologists, blinded to the study, for a number of radiologic parameters, including central node necrosis. Multivariate logistic regression was used to identify parameters independently predicting pathologic ECS. Results For both neuroradiologists, central node necrosis was a significant predictor of ECS, with high interrater agreement (kappa = 0.71). On multivariate analysis, only central node necrosis independently predicted ECS (odds ratio [OR] = 12.1; 95% confidence interval [CI] = 1.24–119). Central node necrosis predicted ECS with 91% sensitivity and 88% negative predictive values. Conclusion Our findings suggest that central node necrosis on preoperative CT scans is strongly associated with the presence of ECS. © 2014 Wiley Periodicals, Inc. Head Neck37: 92–96, 2015